2018
DOI: 10.1016/j.burns.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between invasive and noninvasive blood pressure measurements in severely burned children

Abstract: Cuff measurements vary widely from those of intra-arterial lines, which have a low complication rate. Intra-arterial lines are advisable when tight control of the hemodynamic response is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
3
8
0
Order By: Relevance
“…Similarly, Joffe et al 30 found a poor degree of correlation in blood pressure readings obtained via IAL versus those obtained via NIBP in critically ill children. The findings of the present study on patients undergoing LE FEE reconstruction along with our previous findings in patients undergoing flap-based breast reconstruction extend the findings of Cambiaso-Daniel et al 29 and Joffe et al 30 to the adult population and suggest that IAL should be used in instances where highly accurate hemodynamic measurements are essential for patient safety and/or surgical success.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, Joffe et al 30 found a poor degree of correlation in blood pressure readings obtained via IAL versus those obtained via NIBP in critically ill children. The findings of the present study on patients undergoing LE FEE reconstruction along with our previous findings in patients undergoing flap-based breast reconstruction extend the findings of Cambiaso-Daniel et al 29 and Joffe et al 30 to the adult population and suggest that IAL should be used in instances where highly accurate hemodynamic measurements are essential for patient safety and/or surgical success.…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings have been reported in the literature by Cambiaso-Daniel et al and Joffe et al; however, these studies were limited to pediatric patients. 16 , 17 These findings suggest that intra-arterial blood pressure monitoring should be used in the place of NIBP in cases where accuracy of measurements is paramount.…”
Section: Discussionmentioning
confidence: 98%
“…The complications associated with intra-arterial catheterization are rare, but exist nonetheless. As few as <1.0% of patients will experience major complications with ABP monitoring, 7 , 8 , 16 but the incidence of minor complications with radial artery catheterization, such as temporary occlusion of the artery, has been cited to be as high as 35%. 8 , 18 Despite its known complications, invasive blood pressure monitoring is indicated in certain procedures and with certain patient populations in which the benefits to use outweigh these risks.…”
Section: Discussionmentioning
confidence: 99%
“…This can probably be explained by the inaccuracy of BP measurements rather than a real limitation of PAAT. In critically ill children, blood pressure measured by cuff does not correlate well with invasively measured blood pressure and cannot replace it when knowing that accurate blood pressure is crucial for minute-to-minute management [42,43]. Similarly, in premature infants, especially at the lower systemic blood pressure range, noninvasive blood pressure measurements do not correlate well with invasive measurements and tend to significantly over-estimate BP, falsely reassuring the providing team [44].…”
Section: Discussionmentioning
confidence: 99%